Development of Ultranarrow‐Bore Open Tubular High Efficiency Liquid Chromatography. Issue 1 (27th November 2021) - Zhou, Yingyan; Guo, Guangsheng; Wang, Xiayan
Comprehensive Summary: Chromatography theory shows that when the inner diameter of the chromatography column is very narrow ( e.g ., 1—2 μm), the maximum efficiency will be produced in liquid chromatography. In addition, the increasing demand for ultrasmall volume sample analysis has produced the trend of narrowing the diameter of the liquid chromatography column. Experiments have verified that ultranarrow‐bore open tubular liquid chromatography (i.d. ≤ 2 μm) has the advantages of small sample requirement and high separation efficiency. However, there also exist huge challenges along with such obvious advantages. This review summarizes the efforts made by our research group and other research groups to develop this field. We hope that in the near future, ultranarrow bore open‐tube liquid chromatography can be successfully and maturely applied to the application of analytes with ultrasmall size and volume such as single‐cell and even subcellular organelles omics research. What is the most favorite and original chemistry developed in your research group? Our research work originated from nanocapillary chromatographic analysis, and then expanded to micro/nanoscale bio‐separation analysis, micro/nanofluidic analysis, and the development of new micro/nano analytical instruments. Currently, our research focuses on single‐cell analysis with temporal and spatial resolution. What is the most important personality for scientific research? Having an enquiring mind; Be diligent, curious, and persistent; Pursuing perfection. What's your hobbies? What's your favorite book(s)? I enjoy cooking and playing Ping‐Pong. My favorite book is The Art of War . Who influences you mostly in your life? My parents. What is your favorite journal(s)? Journal of the American Chemical Society, which is the top international academic journal in the field of chemistry and values novelty. Could you please give us some advices on improving Chinese Journal of Chemistry? Pursue high quality, highlight the characteristics, strive for excellence, enable fast review and publication. Abstract : Ultranarrow‐bore open tubular liquid chromatography brings many advantages due to the ultrasmall size of the inner diameter of the columns and will have broad application prospects in various fields.